2015
DOI: 10.1007/s11255-015-1134-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in the outpatient setting: clinical characteristics, risk factors, and outcome

Abstract: Hyponatremia is prevalent among elderly, especially in women and with thiazide diuretics. Apart from the trend toward sodium depletion observed in healthy elderly which occurs due to changes in the tubular handling of sodium, a multifactorial etiology including thiazides seems to predict the occurrence and the severity of hyponatremia. Hyponatremia may be a significant cause of mortality in seniors. A relatively younger age, male gender, association of cirrhosis, malignancy, and hypoalbuminemia predict mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…Hyponatremia is one of the major side effects of diuretic treatment in hypertensive patients. 1,4,14,15 It may be asymptomatic, but it is associated with increased morbidity and may be life-threatening. 3,5,6,16 The exact mechanism by which thiazide diuretics induce hyponatremia is not completely understood, but it has been suggested to be related to increased water intake and over-secretion of arginine vasopressin (antidiuretic hormone).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyponatremia is one of the major side effects of diuretic treatment in hypertensive patients. 1,4,14,15 It may be asymptomatic, but it is associated with increased morbidity and may be life-threatening. 3,5,6,16 The exact mechanism by which thiazide diuretics induce hyponatremia is not completely understood, but it has been suggested to be related to increased water intake and over-secretion of arginine vasopressin (antidiuretic hormone).…”
Section: Discussionmentioning
confidence: 99%
“…18,22 Other investigators also reported that low BMI and older age are associated with hyponatremia. 4,15 Based on the analysis models that we performed in the present study, it appears that HDL-C levels are more important than these previously described factors: this is first demonstrated by the fact that HDL-C holds more information content in the GBM predictive model than BMI, age, and sex altogether; second, when lipid levels are not used to build the predictive model, the prediction accuracy decreases significantly, and the BMI takes HDL-C's place as the most informative factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most common electrolyte disorder, 53 and the most common cause of such in the outpatient setting is thiazide diuretic use. 54 Hyponatremia can occur in euvolemic states (SIADH), hypervolemic states (heart failure, cirrhosis), or hypovolemic states (dehydration with poor intake). Hypotonic hyponatremia is the most common and relevant form of the disorder.…”
Section: Electrolytementioning
confidence: 99%
“…Symptoms of hyponatremia are initially subtle, nonspecifics, and difficult to recognize. They mostly manifest as neurological changes, which ranges from altered personality, lethargy and confusion to seizures, coma and death in severe cases [2,77] Modified from [58,59]. Table 3.…”
Section: Clinical Featuresmentioning
confidence: 99%